The teen's guide to world domination : advice on life, liberty, and the pursuit of awesomeness - Shipp, Josh. (St. Martin's Griffin, 2010)
Teen advice guru and motivational speaker Shipp delivers a hilarious, inspirational guide for the millennial generation that covers everything from broken self-esteem to family crisis to what to do after high school.